PENGARUH BEBAN PAJAK DAN KEPEMILIKAN ASNG TERHADAP KEPUTUSAN TRANSFER PRICING - Ningsih, Harianti; Dewanti, Yopy Ratna (POLITEKNIK LP3I JAKARTA, 2023)
Article 21 Income Tax is one type of Income Tax imposed on income in the form of salary, wages, honorarium, allowances, and other payments received or obtained by domestic individual taxpayers in connection with work or position, services, and activities. Therefore, government agencies and companies that pay employees or employees must implement the calculation of Income Tax Article 21 on the income received by their employees every month. This research was conducted at PT. Trimuda Eka Bhakty. In making this Final Project Report the author wants to know whether the application of calculation, deduction, depositing and reporting income tax article 21 for permanent employees of PT. Trimuda Eka Bhakty is in accordance with Taxation Law No. 36 of 2008 concerning Income Tax. This study uses descriptive research methods with qualitative approaches, and data collection techniques used are by observation, informants and literature. The results of this Final Project Report indicate that PT. Trimuda Eka Bhakty in the application of calculations, deductions and deposits is in accordance with the applicable provisions, while in the income tax reporting article 21 for employees there is a delay of several months so that it is not fully in accordance with the applicable tax regulations.Keywords: Article 21 Income Tax, PT. Trimuda Eka Bhakty, tax regulations